2016
DOI: 10.1111/iju.13093
|View full text |Cite
|
Sign up to set email alerts
|

Lower calyceal and renal pelvic stones in preschool children: A comparative study of mini‐percutaneous nephrolithotomy versus extracorporeal shockwave lithotripsy

Abstract: Objectives: To compare outcomes of the mini-percutaneous nephrolithotripsy technique and extracorporeal shockwave lithotripsy for lower calyceal and renal pelvic stones in preschool children. Methods: From January 2010 to December 2014, single renal pelvic or lower calyceal calculi 10-25 mm in size in children (age ≤6 years) treated by either extracorporeal shockwave lithotripsy (64 patients) or the mini-percutaneous nephrolithotripsy technique (54 patients) were included. Extracorporeal shockwave lithotripsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…When compared with SWL for children with renal stone burden of 1–2.5cm, mini-PCNL was found to be more efficacious with a higher stone-free rate although with one randomized trial noting longer operative time, higher radiation exposure, and more complications. 57,58 Similarly, Saad and associates noted a higher stone-free rate (96% vs. 71%) at the expense of higher complication rate in children with renal stone burden >2cm randomized to undergo PCNL compared with URS. 59 The authors noted a 14% blood transfusion rate with PCNL compared to 0% with URS.…”
Section: Acute Managementmentioning
confidence: 97%
“…When compared with SWL for children with renal stone burden of 1–2.5cm, mini-PCNL was found to be more efficacious with a higher stone-free rate although with one randomized trial noting longer operative time, higher radiation exposure, and more complications. 57,58 Similarly, Saad and associates noted a higher stone-free rate (96% vs. 71%) at the expense of higher complication rate in children with renal stone burden >2cm randomized to undergo PCNL compared with URS. 59 The authors noted a 14% blood transfusion rate with PCNL compared to 0% with URS.…”
Section: Acute Managementmentioning
confidence: 97%
“…In total, 13 articles were included in this quantitative synthesis [1527]. There were 3 randomized controlled trials [17, 21, 24] (RCTs) (LE: 2b), 1 prospective case controlled study [16] (LE: 3b) and 9 retrospective case controlled studies [15, 1820, 22, 23, 2527] (LE: 3b) (Table 1). Seven nonrandomized studies were relatively high (NOS: 6 of 9 points) and 3 nonrandomized studies were medium (NOS: 5 of 9 points) in methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Lower calyceal stones have a poorer clearance rate as compared to renal pelvic, upper, and mid calyceal stones (52). Lower calyceal stone clearance by ESWL is dependent on anatomical factors such as lower calyceal infundibular width, length, and infundibulopelvic angle (53, 54).…”
Section: Extracorporeal Shockwave Lithotripsymentioning
confidence: 99%
“…Retrospective comparative studies have indicated that mini PCNL provides at least similar stone-free rate for moderate-size stones in comparison to RIRS (61). ElSheemy et al also demonstrated superior results with mini PCNL (14FG) for renal calculi of 10–25 mm in preschool children in comparison to ESWL with comparable complication rates but a longer hospital stay (52).…”
Section: Percutaneous Nephrolithotomymentioning
confidence: 99%